IMPLEMENTASI PEMBELAJARAN AL-QUR’AN METODE LITTAQWA DI SDIT NUR HIDAYAH SURAKARTA DAN METODE KARIMAH DI MI NURUL KARIM KARANGANYAR TAHUN AJARAN 2019/2020 - Bayu Mufti Sugiyanto; Ari Anshori; M Muthoifin (Universitas Muhammadiyah Surakarta, 2020)
This research aims to describe the implementation of the Littaqwa method in learning the Qur’an at SDIT Nur Hidayah Surakarta and the karimah method at MI Nurul Karim Karanganyar and describe the supporting and inhibiting factors. This type of research is field research, with a qualitative approach. The object of research is SDIT Nur Hidayah Surakarta and MI Nurul Karim Karanganyar. Research subjects include the Principal / Madrasa, al-Qur’an learning coordinator, teachers who teach the al-Qur’an and several students. Data collection techniques are done by observation, interview and documentation. Data analysis was performed descriptively qualitative. The results showed that the main target of learning the Koran at SDIT Nur Hidayah was an understanding of the principles of recitation with the target of memorization of at least 2 juz (juz 29 and 30) and memorization of hadith, the learning method used was littaqwa by applying three learning models namely classical with the teacher, independent classical and one-on-one classics. Evaluations are conducted at the end of each meeting and evaluation of volume increases. While in MI Nurul Karim the target of memorization is owned by ± 5 juz graduates (juz 26, 27, 28, 29 and 30), learning using the karma method which has four teaching principles namely talqin, tikrar, tahqiq and tabyin. Evaluation of learning is done in 3 stages, namely the class exam, juziyyah and the peak is the best tahfidz school overall champion test. The implementation of al-qu’an learning has implemented a constructivism approach in choosing learning strategies, as an effort to create a learning process that is appropriate to the character of students.Supporting factors that encourage the implementation of the learning of the Qur’an include the standardization of qualified educators and workshops specifically Tahfidz teachers, innovation and strategies in delivering learning, using teaching aids and student handbooks that are easily understood, having Iad classes specifically for 1 grade of elementary school , has its own distinctive tone or hum. While the obstacles faced include students who are not fluent in reading the Koran, lack of guidance and support from families for children, and there are still children who lack concentration and attention when the learning process takes place.